Sinergi Peran Orang Tua dan Dukungan Emosional terhadap Perkembangan Sosial serta Akademik Siswa di SDIT Bina Insan Cita Babelan - Oktafiana Kiranida; Farouq Fathurrahman; Susi Handayani Br.Lubis; Anisa Melamita (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to enhance parents’ awareness and involvement in supporting the academic and social development of children at the Integrated Islamic Elementary School. The activities will focus on the role, engagement, and emotional support of parents as crucial factors in fostering children’s educational processes. By involving parents, teachers, and students, the program will provide a deeper understanding of the importance of parental roles in creating an environment that supports children’s education, both academically and socially. Through counseling sessions, training, and focused group discussions (FGDs), the program seeks to strengthen communication and collaboration between parents and the school. It is expected that, through these activities, parents will gain a better understanding of how to provide effective emotional support for their children’s development, while also building a harmonious relationship between home and school. The outcomes of this community service program are expected to contribute positively to creating a more supportive educational environment for children at the Integrated Islamic Elementary School.